2016
DOI: 10.1007/s11814-015-0295-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sorbitan monostearate concentration on the thermal, mechanical and drug release properties of oleogels

Abstract: The current study describes the effect of the concentration of Span 60 (gelator) on the properties of oleogels. Mustard oil was chosen as the representative vegetable oil. Microscopy showed that an increase in the gelator concentration resulted in the increase in the gelator network density. Thermal studies (crystallization kinetics and differential scanning calorimetry) indicated a 2-stage crystallization process. An increase in the gelator proportion resulted in the increase in the compatibility amongst the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 29 publications
2
28
0
3
Order By: Relevance
“…The formation of plate-like structure hinders solute migration [14]. On the contrary, the formation of fiber-like structures promotes solute migration [32]. Since the addition of stearic acid promotes formation of fibrous structures, which result in the formation of a mesh network, it was expected that the solute (in this case drug molecules) migration would be promoted.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of plate-like structure hinders solute migration [14]. On the contrary, the formation of fiber-like structures promotes solute migration [32]. Since the addition of stearic acid promotes formation of fibrous structures, which result in the formation of a mesh network, it was expected that the solute (in this case drug molecules) migration would be promoted.…”
Section: Discussionmentioning
confidence: 99%
“…The test was carried out for 2 h. The cumulative drug release (CPDR) profiles were determined (Figs. 12(a) and 12(b)) [14]. It was observed that the release of the drug was higher during iontophoresis as compared to the passive study.…”
Section: Resultsmentioning
confidence: 93%
“…In vitro drug release from organogels was performed through a dialysis membrane (HIMEDIA ® LA 330-5MT) in modified Franz diffusion cell [26]. Accurately weighed drug-loaded sample containing drug equivalent to 4 mg was placed in the donor compartment and the receptor chamber containing phosphate buffer (pH 5.8) was maintained at 32°C ± 0.5°C.…”
Section: In Vitro Drug Release Studymentioning
confidence: 99%